2017
DOI: 10.1177/2292550317731762
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Harvesting of Omental Flaps for Breast Reconstruction—A Review of the Literature and Outcome Analysis

Abstract: Omentum use is safe and has advantages in breast reconstruction where other options are limited including a natural feeling and minimal donor site morbidity if harvested laparoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…4 Our second concern is that body mass index (BMI) greater than 35 kg/m 2 is considered a contraindication factor for omental flap because of safety concerns expressed by some authors. 5 However, the author did not mention the data regarding the celiac artery problems and BMI in the present study. We would like to emphasize that preexisting celiac artery problems and higher BMI scores could mask the outcomes, because these parameters can affect the omental flap coverage therapy.…”
mentioning
confidence: 75%
“…4 Our second concern is that body mass index (BMI) greater than 35 kg/m 2 is considered a contraindication factor for omental flap because of safety concerns expressed by some authors. 5 However, the author did not mention the data regarding the celiac artery problems and BMI in the present study. We would like to emphasize that preexisting celiac artery problems and higher BMI scores could mask the outcomes, because these parameters can affect the omental flap coverage therapy.…”
mentioning
confidence: 75%
“…More importantly, several episodes of excessive coughing after the surgery is a risk of dehiscence in the abdominal wound, especially after the traditional approach, which should be repaired immediately, but the laparoscopic approach minimizes it. 33 Various complications such as mesenteric hematoma, 7,10,11 conversion to laparotomy, 10,11,31 cardiovascular problems, 31 pedicle injury, 5,7,34 and hernia in donor site 5,7,34 have been reported as a result of the harvesting of free intestinal flaps laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…First, vascular pedicle injuries are more common with the laparoscopic approach than with the traditional approach. 5,7,34 It is probably related to its deeper location and as it is more demanding to dissect around the highly rich vascular arcade and intestinal tissues. Second, there is a possible risk of damage to the serosa layer of intestine by electrocautery, which may create intraabdominal adhesions in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Zaha (14), the largest reported series on oncoplastic surgery with an LHPOF, showed the promising oncological safety and clinical benefits of this procedure. The free omental flap used for breast reconstruction in this procedure has been proven to be reliable and safe (1,15), and LHPOF has been shown to cause the least amount of donor site deformity (5,10,13,14,16,17). However, in previous studies, either open surgery was used for mastectomy or the omental flap was taken from another incision in the abdominal wall, resulting in obvious scars on the chest and abdominal wall and less than ideal aesthetic results.…”
Section: Introductionmentioning
confidence: 99%